The influence of joint line position on functional outcome in primary total knee arthroplasty - Gupta, Nikhil; Singh, Rajesh; Saxena, Akash (International Journal of Research in Orthopaedics, 2021)
Background: To find out the cut off for position of joint line which will provide a good functional outcome. Methods: 58 patients underwent total knee arthroplasty using standard medial parapatellar approach were included in this study. Pre-operative and post-operative radiological joint line were assessed. Pre-operative and post-operative functional assessment were done using oxford knee score and International knee society score. functional outcome was assessed at 1, 3 and 6 months. Influence of post-operative joint line change on functional outcome was assessed on follow up visit in 6th month. Results: Of 58 patients studied, mean age ± SD was 69.0±7.5 years. Joint line elevation of 36, 16, 8 and 2 patients were between 0-2, 2-4 4-8 and>8 mm respectively with mean ± SD of joint line elevation of 2.24±2.07 mm in the group. Mean OKS-knee score at 6 months follow-up of study group was 36.60 with mean IKSS-knee score of 38.17 at 6 months follow up of group<4 mm which was significant (p<0.05) when compared to mean IKSS-knee score at 6 months follow up of group>4 mm (28.40). Conclusions: It was concluded that joint line restoration is necessary for getting a good functional outcome after primary total knee arthroplasty. The functional outcome of patients with joint line elevation between 4-8mm showed inferior outcomes in comparison to the patients with joint line elevation within 4 mm.